2017
DOI: 10.1057/cep.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

An emerging EU strategic narrative? Twitter communication during the EU’s sustainable energy week

Abstract: This paper approaches the subject of the global recognition of the term 'Normative Power Europe' in external energy governance by engaging with the concept of strategic narratives.The paper considers reactions to the European Union (EU) as a normative energy actor within a tripartite scheme of strategic narrative formation, projection and reception (Miskimmon et al, 2013;Roselle et al, 2014). The definition of a narrative suggests the presence of an actor, an action, a goal or intention, a scene and instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…That same study concluded that more public opinion research is needed to enable a people-centric just transition. Tweets related to energy-related topics from the EU Sustainability Energy Week were used to map stakeholders' significant energy concerns and emotional tendencies towards these issues by Bain and Chaban 71 . Veltri and Atanasova 72 explored the network topology of climate change tweets and news media articles for automated text classification according to psychological process categories.…”
Section: Towards People-centric Climate Action In Building Sector Emi...mentioning
confidence: 99%
“…That same study concluded that more public opinion research is needed to enable a people-centric just transition. Tweets related to energy-related topics from the EU Sustainability Energy Week were used to map stakeholders' significant energy concerns and emotional tendencies towards these issues by Bain and Chaban 71 . Veltri and Atanasova 72 explored the network topology of climate change tweets and news media articles for automated text classification according to psychological process categories.…”
Section: Towards People-centric Climate Action In Building Sector Emi...mentioning
confidence: 99%
“…The proliferation of digital technologies could mediate the effectiveness of strategic narratives among the targeted national or international communities. On the one hand, international actors utilize digital tools to disseminate strategic narratives and win support in international targeted communities (Bain and Chaban, 2017). Populist leaders and parties worldwide thrive in the distinctive architecture of digital media to spread nationalistic content in the promotion of political viewpoints (Mihelj and Jiménez-Martínez, 2021).…”
Section: Everydayness and Nationalism In Securitization On Social Mediamentioning
confidence: 99%
“…One the other hand, social media has offered the realm allowing for various forms of vernacular practices (Szarecki, 2020). It has provided citizens with the opportunity to better access information, participate in political debates (Fuller et al, 2018), and to engage with international affairs (Bain and Chaban, 2017). Social media influencers (abbreviated as influencers) formed by regular internet users who are devoted to building followings express their stance toward social-political affairs (Abidin, 2021; Abidin, 2019).…”
Section: Everydayness and Nationalism In Securitization On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Ghazali et al underscored the importance of public awareness in mitigating the negative externalities associated with CO 2 emissions, climate change, and carbon capture and storage (CCS) through a survey of residents in five states of Malaysia [81]. The analysis of the EU's social media communication efforts presented the likely view [82], while Gupta showed how the power of social media can be leveraged for social goods such as the provision of micro lending in India [83].…”
Section: Review Of Topicsmentioning
confidence: 99%